Modeling Organisational Management Structure of the United University - Svetlana E. Maykova (National Research Mordova State University, 2017)
Introduction: higher education institutions are currently going through intensive reorganization processes that also have effect on university organisational management structures. This is caused by the mismatch between traditional linear-functional structures of management and current situation in the market of educa¬tional services and by the inability to respond flexibly to changes in the external environment. The purpose of the article is to develop a conceptual model of the university management organisational structure as well as alternative scenarios for transition to the above model based on the analysis of domestic and foreign approaches pertaining to the development of university management structures formed due to the merging of separate universities, scientific organisations, institutions and colleges. Materials and Methods: the conceptual article is based on the analysis of works by domestic and foreign authors in the field of development of organisational design and management structure of a modern university. To achieve this goal, the authors made a comparative analysis between organizational management structures of domestic federal universities and international universities, reorganized in the process of merging. The scenario approach allowed to determine various versions of the organisational management structure model that ensures positive results following the integration of vari ous scientific and educational organisations. Results: the analysis of approaches to designing organisational management structures of an educational institution was made, including: organisational management structures of federal universities, implemented approaches to development of management structures of leading foreign universities. The goals and tasks of the transition to the new organisational design of the university, the principles and requirements for the formation of an effective organisational structure of management are substantiated. Based on profilisation criteria, the provisional structure of the scientific and educational institutions of the merged university is proposed. The analysis of domestic and international approaches to the development of university management structures allowed to put forward alternative scenarios for the formation of the organisational management structure model of a united university for the implementation of priority directions of its development. Discussion and Conclusions: the proposals and recommendations following the results of the research seek to create conditions for effective interaction between the subdivisions of the united university, optimisation of the managerial and organisational functions of the leadership of educational and research institutions. For universities originated after the merging of separate universities, scientific organisations, institutes, colleges, variants of the contour model of the organisational management structure are proposed. Those proposals are universal during organisational merging of universities.